The Evaluation of Fiscal Decentralization Implementation - Rudy Badrudin; Claudia Astika Putri Mayangsari (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2023)
The objective of study is conducted  in order to evaluate the fiscal decentralization in Central Java Province by analyzing the effect of fiscal decentralization on capital expenditure, economic growth, and social welfare in 35 districts in Central Java Province based on data from 2015 to 2019 with capital expenditure and economic growth as intervening variable. The Central Java Province is a province who does not have regional divisions so its originality or authenticity of the territorial integrity of the regional autonomy will be seen into force since 2001. The year of 2015 to 2019 is  a 15-years period of fiscal decentralization implementation in Indonesia after 2001. The analytical method used is based on the Partial Least Square (PLS) which follows the structural equation  model (SEM) model for testing hypothesis (α = 5%). The findings of study are fiscal decentralization has a positive significant effect on capital expenditure, economic growth, and social welfare; capital expenditure has a negative significant effect on economic growth but has a positive significant effect on social welfare; and economic growth has a positive significant effect on social welfare in regency and city in Central Java Province.